Progressive Impairment of NK Cell Cytotoxic Degranulation Is Associated With TGF-β1 Deregulation and Disease Progression in Pancreatic Cancer - Jun, Eunsung; Song, Ah Young; Choi, Ji-Wan; Lee, Hyeon Ho; Kim, Mi-Yeon; Ko, Dae-Hyun; Kang, Hyo Jeong; Kim, Seong Who; Bryceson, Yenan; Kim, Song Cheol; Kim, Hun Sik (Frontiers in Immunology, 2019)
Natural killer (NK) cells are key effectors in cancer immunosurveillance and can be used as a prognostic biomarker in diverse cancers. Nonetheless, the role of NK cells in pancreatic cancer (PC) remains elusive, given conflicting data on their association with disease prognosis. In this study, using conventional K562 target cells and complementary engineered target cells providing defined and synergistic stimulation for NK cell activation, a correlation between impaired NK cell cytotoxic degranulation and PC progression was determined. Peripheral blood mononuclear cells from 31 patients with newly diagnosed PC, 24 patients with non-malignant tumors, and 37 healthy controls were analyzed by flow cytometry. The frequency, phenotype, and effector functions of the NK cells were evaluated, and correlations between NK cell functions and disease stage and prognosis were analyzed. The results demonstrated that effector functions, but not frequency, of NK cells was progressively decreased on a per-cell basis during PC progression. Impaired cytotoxic degranulation, but not IFN- production, was associated with clinical features indicating disease progression, such as high serum CA19-9 and high-grade tumors. Significantly, this impairment correlated with cancer recurrence and mortality in a prospective analysis. Furthermore, the impaired cytotoxic degranulation was unrelated to NKG2D downregulation but was associated with increased circulating and tumor-associated TGF-1 expression. Thus, NK cell cytotoxic activity was associated with PC progression and may be a favorable biomarker with predictive and prognostic value in PC.